Repeated Anatomical Pulmonary Resection for Second Primary Nonsmall‐Cell Lung Cancer: Safety and Short‐Term Outcomes - Céline Forster; Louis‐Emmanuel Chriqui; Etienne Abdelnour‐Berchtold; Matthieu Zellweger; Jean Yannis Perentes; Thorsten Krueger; Michel Gonzalez (Thoracic Cancer)
ABSTRACT Background Repeated anatomical pulmonary resections in second primary nonsmall‐cell lung cancer (NSCLC) pose significant challenges due to prior surgery. This study evaluates the feasibility and short‐term outcomes of repeated anatomical pulmonary resections for second primary NSCLC. Method We retrospectively reviewed all consecutive cases of repeated anatomical pulmonary resections for second primary NSCLC performed in our institution from January 2014 to December 2023. Results A total of 55 patients (median age 68 years; interquartile range [IQR]: 61.5–72) underwent repeated anatomical pulmonary resections for second primary NSCLC. Adenocarcinoma predominated in both primary (78.2%) and secondary (76.4%) cases. Video‐assisted thoracoscopy (VATS) approach was used in 94.5% and 96.4% for first and repeated resection, respectively (p = 0.647). The extent of pulmonary resection differed between first and repeated resection, with a predominance of lobectomy during first resection (56.4%) and segmentectomy during repeated resection (85.5%, p < 0.001). We did not observe any significant difference in postoperative overall morbidity after first and repeated resection (23.6% vs. 40%, p = 0.065). However, there was an increased incidence of atrial fibrillation (16.4% vs. 0%) and prolonged air leak (> 5 days) after repeated resection (25.5% vs. 5.5%, p = 0.008). The median length of hospital stay was similar after first and repeated resection (5 vs. 5 days, p = 0.089). The three‐year overall survival (OS) was 73% after first resection and 87% after repeated resection. Overall disease recurrence rate was not statistically different between first and repeated resection (1.8% vs. 3.6%, p = 0.558). Conclusion Our series demonstrated that second primary NSCLC can be safely managed by VATS segmentectomy, yielding favorable short‐term survival and low recurrence rates.